2021
DOI: 10.1186/s12879-021-06192-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, species distribution and antifungal susceptibility of Candida albicans causing vaginal discharge among symptomatic non-pregnant women of reproductive age at a tertiary care hospital, Vietnam

Abstract: Background Vaginal candidiasis is frequent in women of reproductive age. Accurate identification Candida provides helpful information for successful therapy and epidemiology study; however, there are very limited data from the Vietnam have been reported. This study was performed to determine the prevalence, species distribution of yeast causing vaginal discharge and antifungal susceptibility patterns of Candida albicans among symptomatic non-pregnant women of reproductive age. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 60 publications
4
14
0
Order By: Relevance
“…Results of the present study concluded that the percent of vaginal Candida infection was 46.8 % of all participants in the study and the most frequent Candida isolate was C. albicans (48.72% of total positive samples). These results are matched with Anh et al [11] study who declared that vaginal yeast colonization in non-pregnant women was 51.3% of participants and C. albicans was the most frequent (51.37%). As Taei et al [12] study declared that the increasing of non-albicans Candida (NAC) species have been recognized significantly during the last two decades, results of the present study showed that the NAC represented 51.28% of total positive samples.…”
Section: Discussionsupporting
confidence: 88%
“…Results of the present study concluded that the percent of vaginal Candida infection was 46.8 % of all participants in the study and the most frequent Candida isolate was C. albicans (48.72% of total positive samples). These results are matched with Anh et al [11] study who declared that vaginal yeast colonization in non-pregnant women was 51.3% of participants and C. albicans was the most frequent (51.37%). As Taei et al [12] study declared that the increasing of non-albicans Candida (NAC) species have been recognized significantly during the last two decades, results of the present study showed that the NAC represented 51.28% of total positive samples.…”
Section: Discussionsupporting
confidence: 88%
“…Candida albicans , which is part of normal vaginal microflora and becomes a robust opportunistic fungal pathogen under various conditions, has been considered the major causes of vulvovaginitis, the medical impact of which also depending on the strain ability to form biofilms [ 4 ]. Regarding treatment, intravaginal and oral azole drugs are currently prescribed for the treatment of VVC and Fluconazole, which is the drug of choice led to the acquisition of inherent resistance, in about 30% of vaginal positive cultures, consequently resulting in failure of therapeutic treatment of the infection [ 5 , 6 ]. Biofilms are communities of microorganisms embedded in an exopolysaccharide matrix that attach to surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, novel solutions and compounds need to be utilized in order to keep up with the evolution of bacterial resistance mechanisms. A prevalence of S. aureus, E. coli, and C. albicans infections associated with the biomedical field has been reported by several authors [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%